If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -3(x + 4) = 11 + -4(x + 1) Reorder the terms: 26 + -3(4 + x) = 11 + -4(x + 1) 26 + (4 * -3 + x * -3) = 11 + -4(x + 1) 26 + (-12 + -3x) = 11 + -4(x + 1) Combine like terms: 26 + -12 = 14 14 + -3x = 11 + -4(x + 1) Reorder the terms: 14 + -3x = 11 + -4(1 + x) 14 + -3x = 11 + (1 * -4 + x * -4) 14 + -3x = 11 + (-4 + -4x) Combine like terms: 11 + -4 = 7 14 + -3x = 7 + -4x Solving 14 + -3x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 14 + -3x + 4x = 7 + -4x + 4x Combine like terms: -3x + 4x = 1x 14 + 1x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 14 + 1x = 7 + 0 14 + 1x = 7 Add '-14' to each side of the equation. 14 + -14 + 1x = 7 + -14 Combine like terms: 14 + -14 = 0 0 + 1x = 7 + -14 1x = 7 + -14 Combine like terms: 7 + -14 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| -5a+6=-4+-7 | | 4.00+2.75=20.50 | | 3(2x+1)-2(5-x)=29 | | 8y-8=4y+4 | | .06z=4.25 | | 2/5*8=z | | 9(3u+11)-14=11u-41-2u | | b^2+15+54=0 | | 2x=4x+7 | | 26-2x=26+2 | | x^2+56=0 | | u^2+6u+13=0 | | 14=2s+10 | | 4x-6=-8 | | -30-5x+7x=8 | | 1.2-x+3.2=x-4 | | 1/5*2=x | | 8x-5(x-15)=4x | | x-6.1=-6.9 | | x-2+7=-3 | | .30-5x+7x=8 | | 6x+(5x-6)=18 | | 4u^7+24u^6+52u^5=0 | | 6x-12-4x=16 | | 6x^2+7x+9=0 | | 3y+16=5x-8 | | x/4=x+2/5 | | x-2+7=3 | | 3z/8=1/5(2z+3) | | 14x^2-27x+9=0 | | x(4x-7y)-7=10 | | 7x-5+2x=-3x-41 |